Directed search of variants in technologies for reengineering of corporate computer networks - Beskorovainyi, V.; Russkin, V. (My University, 2021)
The formalization of the multicriteria task of system reengineering of a corporate computer network is proposed. It presupposes structural, topological, parametric and technological optimization of the network in terms of a complex “effect-cost” indicator. The parameters of the quality of the variants are detailed in the form of particular criteria of costs, efficiency, reliability and survivability. This allows us to reduce the multicriteria task to a traditional optimization task with a scalar criterion. The proposed approach to the formation of a subset of effective ones already at the stage of generation of feasible variants can significantly reduce the time and capacitive complexity of methods for solving the task of network reengineering. For the final choice of the reengineering variant by the decision maker, it is proposed to reduce to the required size the subsets of effective alternatives using the known combined method
Keywords: automation of design; reengineering of corporate computer networks; multicriteria optimization; decision making; directed search of options